Inverse diffraction for the Atmospheric Imaging Assembly in the Solar Dynamics Observatory. (17th August 2015) - Torre, G; Schwartz, R A; Benvenuto, F; Massone, A M; Piana, M
Abstract: The Atmospheric Imaging Assembly in the Solar Dynamics Observatory provides full Sun images every 12 s in each of 7 extreme ultraviolet passbands. However, for a significant amount of these images, saturation affects their most intense core, preventing scientists from a full exploitation of their physical meaning. In this paper we describe a mathematical and automatic procedure for the recovery of information in the primary saturation region based on a correlation/inversion analysis of the diffraction pattern associated to the telescope observations. Further, we suggest an interpolation-based method for determining the image background that allows the recovery of information also in the region of secondary saturation (blooming).